(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic has rendered numerous impacts on society, especially to caregivers of older adults, who are facing many tasks. These elevated number of demands and modifications can affect these caregivers’ mental health. This study aimed to gather empirical evidence on existing researches about the impact of caregiver’s mental health of older adults during the COVID-19 pandemic. This rapid systematic review, developed from international and Brazilian databases from January/2020 to April/2021, identified 4714 potentially relevant articles, published in English and Portuguese. Eighteen (18) articles that potentially met the inclusion criteria were screened and read. Eleven of them met the inclusion criteria and were selected for this review. Caregivers of older adults demonstrate different psychological manifestations such as higher levels of stress, anxiety, sleep problems, depression, somatic symptoms, and poor quality of life. Those can directly influence the care provided to the older adults. Knowing the effects on the caregivers can be conducted psychological interventions to prevent and minimize impacts in their lives.